Microalgae assisted bioremediation of dairy side-streams - Lia, Fahmida (My University, 2025)
Rising global demand for food, water, and energy has accelerated the dairy industry operation generating large volume of effluent, rich in complex mix of organic matter, and micro- and macronutrients that causes eutrophication if discharged untreated. Currently, microalgae have emerged as a promising sustainable solution for treating these dairy effluents. This study evaluated seven microalgal strains (Scenedesmus sp., Tetradesmus obliquus, Monoraphidium contortum, Chlorella sorokiniana Chlorella vulgaris, Chlorella sp., and Scenedesmus sp.) from Nordic culture collections (NORCCA and HAMBI) for their acclimatization, growth, and nutrient removal in simulated dairy wastewater (SDWW). Preliminary screening in 20% SDWW was conducted under photoautotrophic, mixotrophic and heterotrophic conditions. Selected strains were further assessed in higher organic load (50% and 100% SDWW). Performances were assessed by measuring optical density, quantum yield, chlorophyll content, and nutrient concentrations, as well as through microscopic observation. Results demonstrated significant dynamic acclimatization of Scenedesmus sp., Tetradesmus obliquus, Monoraphidium contortum and Chlorella sorokiniana to SDWW for energy acquisition even at 21˚C under mixotrophic treatment supplemented with 1% CO2. In heterotrophic conditions, the growth was significantly retarded for all strains. When acclimated to 50% and 100% SDWW, among the selected strains Tetradesmus obliquus, and Chlorella sorokiniana showed promising acclimatization, biomass and chlorophyll production and nutrient removal efficiency. For long-term assessment towards continuous mode, fed-batch trials revealed that Chlorella sorokiniana outperformed Tetradesmus obliquus in the co-culture. The findings demonstrated the potential of Chlorella sorokiniana and Tetradesmus obliquus as the promising candidates for bioremediation of real dairy wastewater.
Keywords: Keywords: bioremediation, dairy effluent, heterotrophy, microalgae, mixotrophy, organic matter, simulated dairy wastewater